1997
DOI: 10.1038/nm1097-1124
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-15 protects from lethal apoptosis in vivo

Abstract: Interleukin-15 shares many biological activities with IL-2 and signals through the IL-2 receptor beta and gamma chains. However, IL-15 and IL-2 differ in their controls of expression and secretion, their range of target cells and their functional activities. These dissimilarities may include differential effects on apoptosis. For example, IL-2 induces or inhibits T-cell apoptosis in vitro, depending on T-cell activation, whereas IL-15 inhibits cytokine deprivation-induced apoptosis in activated T cells. Studyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
216
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 297 publications
(226 citation statements)
references
References 24 publications
9
216
1
Order By: Relevance
“…In fact, the property of IL-15 to substitute the growth-promoting effect of IL-3 of the genetically engineered BA/F3 cells, diminishing the number of apoptotic cells and resulting in survival of 80 -90% of the cells, appears to be in accordance with its well-documented antiapoptotic function (10,27,28).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In fact, the property of IL-15 to substitute the growth-promoting effect of IL-3 of the genetically engineered BA/F3 cells, diminishing the number of apoptotic cells and resulting in survival of 80 -90% of the cells, appears to be in accordance with its well-documented antiapoptotic function (10,27,28).…”
Section: Discussionmentioning
confidence: 88%
“…Goat anti-mouse, goat anti-rabbit, and rabbit anti-goat HRP conjugates (Amersham Life Science, Little Chalfont, U.K.) were used as secondary Abs. IL-15-IgG2b fusion proteins were produced, as previously described (10).…”
Section: Cytokines Abs and Fusion Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-15, a growth factor, also protects many cell types from apoptotic death (18,19,40). To determine whether IL-15 elicits antiapoptotic effects upon RA FLS, the effect of IL-15 on the expression of mRNA encoding antiapoptotic proteins Bcl-2 and Bcl-x L were examined.…”
Section: Endogenous Il-15 Is Responsible For Enhanced Expression Of Bmentioning
confidence: 99%
“…It has been shown that IL-15 is a potent inhibitor of apoptotic pathways in lymphocytes, inducing antiapoptotic molecules such as Bcl-2 and Bcl-x L (15)(16)(17)(18). Previous studies have shown that IL-15 is critical for the maintenance of NK cells by up-regulating expression levels of Bcl-2 (18 -20).…”
mentioning
confidence: 99%